2016
DOI: 10.1103/physrevlett.116.246403
|View full text |Cite
|
Sign up to set email alerts
|

Bulk Fermi Surface of Charge-Neutral Excitations inSmB6or Not: A Heat-Transport Study

Abstract: Recently there have been increasingly hot debates on whether a bulk Fermi surface of chargeneutral excitations exists in the topological Kondo insulator SmB6. To unambiguously resolve this issue, we performed the low-temperature thermal conductivity measurements of a high-quality SmB6 single crystal down to 0.1 K and up to 14.5 T. Our experiments show that the residual linear term of thermal conductivity at zero field is zero, within the experimental accuracy. Furthermore, the thermal conductivity is insensiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 48 publications
2
35
0
Order By: Relevance
“…In other words, as the bulk resistivity diverges as T → 0, the Lorentz number for the heat carrying quasiparticles also diverges. Thus the thermal conductivity and heat capacity data very strongly suggest the presence of highly mobile and gapless neutral fermion excitations in zero field, which are not observed in SmB 6 .…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…In other words, as the bulk resistivity diverges as T → 0, the Lorentz number for the heat carrying quasiparticles also diverges. Thus the thermal conductivity and heat capacity data very strongly suggest the presence of highly mobile and gapless neutral fermion excitations in zero field, which are not observed in SmB 6 .…”
mentioning
confidence: 89%
“…At zero field, despite ρ xx being far larger than that of conventional metals, a sizable linear temperature dependent term in the thermal conductivity is clearly resolved in the zero-temperature limit (κ xx /T (T → 0) = κ 0 xx /T = 0), analogous to normal metallic behaviour. Such a residual κ 0 xx /T term at zero field, which is absent in SmB 6 [3,6,7], leads to a spectacular violation of the Wiedemann-Franz law: the Lorenz ratio L = κ xx ρ xx /T is 10 4 -10 5 times larger than that expected in conventional metals. These data indicate that YbB 12 is a charge insulator but a thermal metal, suggesting the presence of itinerant neutral fermions.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[1,2] In some mixed-valence compounds, however, electron-electron interactions lead to the opening of a charge gap at low temperature, resulting in an insulating state which can be called a mixed-valence insulator (MVI). The nature of this insulating state has attracted much attention in recent years, following a proposal that some MVIs could host an interaction-induced three-dimensional topological insulator state [3][4][5], and the subsequent experimental observation of quantum oscillations coexisting with the insulating state in the MVIs SmB 6 [6,7] and YbB 12 [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…This report has of course aroused great interest and also raises a question as to how it relates to the earlier dHvA study [47] that reported two-dimensional surface states. Each of two recently published papers [98,99] offer both theoretical and experimental perspectives on this new and very different possibility for exciting physics in SmB 6 .…”
Section: Special Aspects Of Ti Narrative For Smbmentioning
confidence: 99%